Breastfeeding in public: a study of attitudes and perception among Malay undergraduates in Universiti Sains Malaysia - Maria Aloysius; Shariffah Suraya Syed Jamaludin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Breastfeeding in public is a bodily issue that is associated with vulgarity and obscenity across cultures in the world. Literature on breastfeeding in public in Malaysia are scarce and this study wants to provide insight into understanding how the Malaysian youth, specifically Malay undergraduates respond towards breastfeeding in public. This qualitative study examines the attitudes and support (acceptance or rejection) among Malay undergraduate students towards breastfeeding in public using the Fredrickson & Robert’s Self Objectification Theory. A sample of 40 Malay undergraduate students, both female and male undergraduates from a Malaysian public university, Universiti Sains Malaysia (USM) were interviewed face to face to determine their attitudes and support towards breastfeeding in public. Braun & Clarke’s thematic analysis were used to develop themes from the data collected from the Malay undergraduates. Seven themes which are discretion, public perception, social taboo, emotions, and hypersexualization of breasts, male gazing and voice of change towards breastfeeding in public were identified. Both Malay female and male undergraduates partially accept breastfeeding in public with discretion. Malay male undergraduates are concerned with the Malaysian public perception towards breastfeeding in public and Malay female undergraduates perceive breasts are sexual objects in comparison to Malay male undergraduates who acknowledge the ‘male gaze’. The support towards breastfeeding in public is more evident among Malay male undergraduates compared to Malay female undergraduates. Breastfeeding in public is perceived as social taboo but Malay undergraduates express the need for better education and exposure on breastfeeding in public.